Aspectos basilares do interacionismo sociodiscursivo: conceitos vygotskyanos revisitados - Corrêa, Marcia Cristina; Melo, Karoline Rodrigues de; Gatto, Vanessa Bianchi (Linguagens & Cidadania, 2016)
In this paper, we will revisit some Vygostkian concepts which underpin the theoretical framework of Socio-Discursive Interactionism (SDI), proposed by Bronckart. From a resumption of studies on Vygotsky about higher mental processes, we will seek to understand the relevance of social relations for language acquisition and, from this, for human psychological development, for their insertion on social activities, and, consequently, for their citizenship education.